2023
DOI: 10.3982/ecta18916
|View full text |Cite
|
Sign up to set email alerts
|

Selection Into Credit Markets: Evidence From Agriculture in Mali

Lori Beaman,
Dean Karlan,
Bram Thuysbaert
et al.

Abstract: We use a two‐stage experiment on agricultural lending in Mali to test whether selection into lending is predictive of heterogeneous returns to capital. Understanding this heterogeneity, and the selection process which reveals it, is critical for guiding modeling of credit markets in developing countries, as well as for policy. We find such heterogeneity: returns to capital are higher for farmers who borrow than for those who do not. In our first stage, we offer loans in some villages and not others. In the sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 64 publications
(106 reference statements)
0
1
0
Order By: Relevance
“…This paper joins an active literature documenting how introducing additional flexibility to credit schemes can improve outcomes. Field and Pande (2010), Field, Pande, Papp, and Rigol (2013), and Beaman, Karlan, Thuysbaert, and Udry (2023 showed that delaying the start of repayment installments, reducing payment frequency, and allowing lump-sum repayments post-harvest reduces borrower transaction costs, and boosts investments and profits. More recently, Battaglia, Gulesci, and Madestam (2023) and Barboni and Agarwal (2022) showed that allowing borrowers to delay repayments improves business outcomes without harming repayment rates; while Aragón, Karaivanov, and Krishnaswamy (2020) showed that a fully flexible credit line improves small business profits by allowing borrowers to quickly respond to changes in the market.…”
Section: Introductionmentioning
confidence: 99%
“…This paper joins an active literature documenting how introducing additional flexibility to credit schemes can improve outcomes. Field and Pande (2010), Field, Pande, Papp, and Rigol (2013), and Beaman, Karlan, Thuysbaert, and Udry (2023 showed that delaying the start of repayment installments, reducing payment frequency, and allowing lump-sum repayments post-harvest reduces borrower transaction costs, and boosts investments and profits. More recently, Battaglia, Gulesci, and Madestam (2023) and Barboni and Agarwal (2022) showed that allowing borrowers to delay repayments improves business outcomes without harming repayment rates; while Aragón, Karaivanov, and Krishnaswamy (2020) showed that a fully flexible credit line improves small business profits by allowing borrowers to quickly respond to changes in the market.…”
Section: Introductionmentioning
confidence: 99%